Initial research notes: mapping the presence of women as titular names of collections housed in memory institutions in Santa Catarina state (PerCursos, 2022)
Taking the Law 18.226 of 2021 as a starting point, which includes the History of Women in the Countryside and the City in the school curriculum of primary education in Santa Catarina state, this article discusses the first moments of a research that aims to map the presence of women as titular names of archives housed in different memory institutions in Santa Catarina. The theoretical-methodological framework of the research is supported by debates that relate memory and history, archives, personal archives, writing of history and women's history. Based on the regional division of the state, the research started with virtual contacts with these institutions and later organization of the data in spreadsheets. Taking into account the few responses received, it was noticed, in addition to a difficulty in understanding the main object of the research, that the presence of women as protagonists is still quite shy in these institutional spaces.
Keywords: collections; women's archives; history writing; memory institutions; Santa Catarina state